2015
DOI: 10.1016/j.jcp.2015.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Boundary conditions and stability of a perfectly matched layer for the elastic wave equation in first order form

Abstract: In computations, it is now common to surround artificial boundaries of a computational domain with a perfectly matched layer (PML) of finite thickness in order to prevent artificially reflected waves from contaminating a numerical simulation. Unfortunately, the PML does not give us an indication about appropriate boundary conditions needed to close the edges of the PML, or how those boundary conditions should be enforced in a numerical setting. Terminating the PML with an inappropriate boundary condition or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…Even when the geometric stability condition is satisfied, however, numerical experiments have also shown that the PML can be unstable [32,33]. For models that satisfy the geometric stability condition, like the acoustic wave equation, recent results [1,2] have revealed the impact of numerical boundary procedures on the stability of discrete PMLs, using high order summation-by-parts (SBP) finite difference method.By the results in [11,16,17] the PML for the acoustic wave equation can be proven well-posed and asymptotically stable. However, the PML and NRBC, involve auxiliary variables and equations that are often not covered by standard DGSEMs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the geometric stability condition is satisfied, however, numerical experiments have also shown that the PML can be unstable [32,33]. For models that satisfy the geometric stability condition, like the acoustic wave equation, recent results [1,2] have revealed the impact of numerical boundary procedures on the stability of discrete PMLs, using high order summation-by-parts (SBP) finite difference method.By the results in [11,16,17] the PML for the acoustic wave equation can be proven well-posed and asymptotically stable. However, the PML and NRBC, involve auxiliary variables and equations that are often not covered by standard DGSEMs.…”
mentioning
confidence: 99%
“…Even when the geometric stability condition is satisfied, however, numerical experiments have also shown that the PML can be unstable [32,33]. For models that satisfy the geometric stability condition, like the acoustic wave equation, recent results [1,2] have revealed the impact of numerical boundary procedures on the stability of discrete PMLs, using high order summation-by-parts (SBP) finite difference method.…”
mentioning
confidence: 99%
“…It is known that simulations of PML can exhibit temporal instability depending on the choice of damping coefficients [11], how the PML is discretized [12], and how it is truncated into a finite domain [13]. It is therefore necessary to check the numerical stability of Eq.…”
Section: Stabilitymentioning
confidence: 99%
“…Yet, by reformulation and carefully choosing the damping coefficients, researchers of [11,12,60] showed that it is possible to regain stability for anisotropic PMLs. More recent studies showed instabilities due to the far-end boundary of the PML, which are then stabilized by backing the PML with a dissipating boundary treatment [13,61,62].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation